COMPARISON OF THE EPICS “MALIKAYI DILOROM” AND “ORZIGUL” (Multidisciplinary Journal of Science and Technology, 2026)
This article compares the epic poem “Malikai Dilorom” by Saodat Mushtariy and the epic poem “Orzigul” in folk literature, and examines their common and different aspects.